Fatigue, sleep disorders, anaemia and pain in the multiple sclerosis prodrome. (February 2021) - Yusuf, Fardowsa LA; Wijnands, José MA; Kingwell, Elaine; Zhu, Feng; Evans, Charity; Fisk, John D; Zhao, Yinshan; Sutherland, Jason M; Patrick, David M; Marrie, Ruth Ann; Tremlett, Helen
Background: There is increasing evidence of prodromal multiple sclerosis (MS). Objective: The aim of this study was to determine whether fatigue, sleep disorders, anaemia or pain form part of the MS prodrome. Methods: This population-based matched cohort study used linked administrative and clinical databases in British Columbia, Canada. The odds of fatigue, sleep disorders, anaemia and pain in the 5 years preceding the MS cases' first demyelinating claim or MS symptom onset were compared with general population controls. The frequencies of physician visits for these conditions were also compared. Modifying effects of age and sex were evaluated. Results: MS cases/controls were assessed before the first demyelinating event (6863/31, 865) or MS symptom onset (966/4534). Fatigue (adj.OR: 3.37; 95% CI: 2.76–4.10), sleep disorders (adj.OR: 2.61; 95% CI: 2.34–2.91), anaemia (adj.OR: 1.53; 95% CI: 1.32–1.78) and pain (adj.OR: 2.15; 95% CI: 2.03–2.27) during the 5 years preceding the first demyelinating event were more frequent among cases, and physician visits increased for cases relative to controls. The association between MS and anaemia was greater for men; that between MS and pain increased with age. Pre-MS symptom onset, sleep disorders (adj.OR: 1.72; 95% CI: 1.12–2.56) and pain (adj.OR: 1.53; 95% CI: 1.32–1.76) were more prevalent among cases. Conclusion: Fatigue, sleep disorders, anaemia and pain were elevated before the recognition of MS. The relative anaemia burden was higher in men and pain more evident among older adults.